Moving Forward While Looking Back: Understanding the Influence of a “Test All” SAK Mandate on Sexual Assault Case Attrition - Pattavina, April (Criminal justice policy review, 2024)
The discovery of thousands of untested sexual assault kits (SAKs) in police jurisdictions across the United States has prompted federal, state, and local agencies to enact policies regarding SAK testing. One legislative response has been to implement “test all” SAK policies. Such policies are expected to remove discretion from the kit submission process and provide crucial forensic evidence needed to guide sexual assault investigations. This study presents the impact of a “test all” policy in a single jurisdiction and investigates whether the increased number of DNA matches expected to come from more testing after implementation increased the likelihood of arrest. Results indicate that the impact of a DNA match on arrest increased after the mandate. The study concludes with a discussion of implications for sexual assault investigations and recommendations for future research.